Tipologia e origem do depósito de ferro hidrotermal da região de São José do Torto-Ce, domínio médio Coreaú, província Borborema - Didoné, Maria Eduarda Zilio (2023)
Mineralizations of iron occur in different geological and/or geotectonic contexts, which stand out: banded iron formations (BIFs); Kiruna-type deposits, related to magmatic-hydrothermal processes; Ironstone-type sedimentary deposits; endomagmatic deposits of Fe-Ti-V oxides; and Skarn-type deposits. The latter result from contact metamorphism between intrusive bodies and carbonate rocks. In the northern part of the Borborema Province, south of the Middle Coreau Domain (MCD) and adjacent to the Transbrasiliano Lineament, significant iron deposits occur hosted in the neoproterozoic siliciclastic and carbonate metasedimentary rocks of the Ubajara Group. These are low-grade metamorphic rocks cut by the post- collisional Mucambo granite (~532Ma), resulting in siliciclastic hornfels and iron-bearing marbles with clinopyroxene and pyrosmalite. The granite is metaluminous, moderately oxidized, composed of quartz, plagioclase, K-feldspar, amphibole, biotite, and accessory minerals such as titanite, apatite, ilmenite, magnetite, and zircon. The mineral assemblages resulting from hydrothermal alteration developed in two stages: an initial stage characterized by subsolidus alterations of iron-magnesian minerals (amphibole and/or biotite) and feldspars, resulting in the formation of magnetite, titanite, chlorite, epidote, and albite; and a more evolved stage marked by quartz, sericite, and magnetite occurring in veins. Petrographic and textural descriptions, coupled with the study of magnetite mineral chemistry, and isotopic analysis of C and O in the metacarbonates of the region, allowed for the identification of different Fe ore types in the Torto Deposit and associated its origin with the Mucambo Granite. The iron ore, dominated by magnetite and subordinately hematite, is associated with the metacarbonates and metasiliciclastics of the Ubajara Group in two styles: massive ore and/or veins, and detrital-lateritic colluvial ore. The vein-style ore varies from centimeter to meter scale, predominantly composed of martitized magnetite, sometimes irregularly replacing the host rock entirely. Magnetite veins are located near the southeastern edge of the Mucambo Granite, in contact with metasedimentary rocks. The detrital-lateritic colluvial ore is the most abundant in the study area, occurring associated with lateritic soil packages in the form of pebbles ranging from 1 to 30 cm. Chemical analyses of magnetites from the Mucambo Granite, veins, and/or veins adjacent to metacarbonates and metasiliciclastics revealed high levels of Al+Mn+Ca (%) and low values of Ti+V (%), which are consistent with hydrothermal skarn-type magnetites. Additionally, the magnetites from the veins in the metacarbonates exhibit the highest values of Mg and Mn, likely reflecting the influence of the host rock or the enrichment of Mg and Mn in the remaining hydrothermal fluid. In granitic magmas, fluids are rich in Si-Fe-W-Na-K-F-Cl-Cu-H2S and H2O and poor in Ca-Mn-Mg. This indicates that these last three elements, when present in anomalous concentrations in magnetites, may be associated with enriched hydrothermal fluids resulting from fluid-rock interactions, especially when the host rocks are dominated by carbonate rocks carrying Mg and Mn, as is the case with the host rocks of the Torto Deposit. The results of isotopic analysis on mineralized and strongly hydrothermally altered metacarbonates indicate that the ore was formed under the influence of magmatic fluids or a mixture of juvenile fluids with connate fluids. This i because their isotopic values approach those of juvenile fluid sources and other studied skarn- type deposits.